Les éléments culturels dans la bande dessinée « de Semarang à Nice : Voyage Interculturel Indonésien - Français » - Sri Maryati; Sri Handayani (Universitas Negeri Semarang, 2024)
Culture can be a characteristic of each region where it originates, resulting in cultural differences between one region and another. Indonesia and France are countries that are rich in culture. This study aims to find and explain cultural elements in the form of ideas, activities, and artifacts in Indonesian and French cultures. The type of research used is descriptive-interpretive, which originates from a comic entitled